Essential oil plants of the Karaganda region - Ishmuratova, Margarita Yu. (Arko” Ltd, 2020)
The monograph presents the results of the study of essential oil plants in the natural flora of the Karaganda region and after introduction into the culture. The complete species composition has been determined, which included 275 species from 130 genera and 35 families. The leading families are Asteraceae, Lamiaceae, Apiaceae, the largest genera Artemisia, Achillea and Thymus. A conspectus of flora has been compiled; an environmental characteristic of species, an analysis of life forms and the degree of prevalence has been given. Plant resources of essential oil plants in nature have been determined. The success of the introduction of essential oil plants in the culture conditions was evaluated; objects promising for industrial cultivation were identified. For some essential oil plants; recommendations for their cultivation have been proposed. Results of study were published in frame of grant ‘The Best High School Teacher – 2019”. The monograph is intended for specialists in the field of botany, plant introduction, workers in botanical gardens, forestry, environmentalists, pharmacists, teachers and students of colleges and universities of biological, pharmaceutical and agricultural profiles. The monograph was recommended for publication at the Council of E.A. Buketov Karaganda University (protocol No. 6 from December, 24, 2020).
Keywords: karaganda region; essential oil plants; flora; karaganda; Zhezkazgan